Essays of Travel - Stevenson, Robert Louis (Saga Egmont, 2023)
This collection includes: THE AMATEUR EMIGRANT: FROM THE CLYDE TO SANDY HOOK.COCKERMOUTH AND KESWICK, AN AUTUMN EFFECT, A WINTER'S WALK IN CARRICK AND GALLOWAY, FOREST NOTES, A MOUNTAIN TOWN IN FRANCE, RANDOM MEMORIES: ROSA QUO LOCORUM, THE IDEAL HOUSE, DAVOS IN WINTER, HEALTH AND MOUNTAINS, ALPINE DIVERSION, THE STUMULATION OF THE ALPS, ROADS, and ON THE ENJOYMENT OF UNPLEASANT PLACES.